A preliminary study of macrofungi in Universiti Teknologi MARA Pahang, Jengka campus - Hashim, Sarina; Mustaffa, Muzamil; Kasim, Jamaludin (Universiti Teknologi MARA, 2010)
Fungi are among the most important organisms because of their vital roles in ecosystem functions. Different kinds of macrofungi have been recognized for thousands of years, but no study on macro fungi has been recorded in Universiti Teknologi MARA (UiTM) Pahang. The objectives of this preliminary study are to identify and to document the macro fungi collected around UiTM Pahang, Jengka Campus. Studies were conducted during rainy season (October 2008 and September 2009) and during dry season (Julai 2009 and January 2010). The researchers collected as many specimens as they could find and recorded the morphology and ecology of the specimens. The classification of species was done based on their reproductive structures or the fruitbody. This study recorded a total of 55 genera of macro fungi from the study area. The largest group was bracket fungi (25 genera), followed by agaric mushrooms (18 genera), boletes (4 genera), ball fungi (3 genera), jelly fungi (2 genera), club fungi (l genera), coral fungi (l genera) and cup fungi (1 genera)